Penerapan Teori Multiple Intelligences Howard Gardner Dalam Pembelajaran Pendidikan Agama Islam - Handal Pratama Putra; M. Hajar Dewantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this study is to describe how the application of Howard Gardner's theory of multiple intelligences in learning Islamic Religious Education (PAI). This type of research is a literature study with a qualitative approach. The method of analysis in this study uses the method of content analysis. The results of this study indicate that there are nine types of intelligence possessed by humans, namely linguistic intelligence, logical-mathematical intelligence, spatial intelligence, musical intelligence, bodily kinesthetic intelligence, intrapersonal intelligence, interpersonal intelligence, naturalist intelligence and existential intelligence. Howard Gardner's theory of multiple intelligences can be applied to the learning of Islamic religious education through various methods, strategies and learning models so that the potential, talents and abilities of students.